Shareholder voting right under the companies and allied matters act, 1990: The philosophy and legal overview - Magaji, Shamsuddeen (2017)
The right to vote at the general is one of the most important rights that belongs to shareholders. This right empowers shareholders to subject the board of directors to account for their stewardship and where the board is found wanting, the shareholders may exercise their voting right to remove and replace the board. In Nigeria, the CAMA 1990 recognised the right of shareholder to vote at the general meeting. However, very few literatures could be found in this area. This study seeks to examine shareholder voting right from both philosophical and legal perspective in order to lay a solid foundation for shareholder voting right in Nigeria. The study will emphasise on the theory of shareholder voting and its relevance to corporate governance by unveiling the objective of shareholder vote as well as the relevant theory to shareholder vote. The study employed doctrinal legal research methodology in obtaining the relevant data. The findings show that this study is one of the very few studies that tries to identify theories that are relevant to shareholder vote in Nigeria. The study maintains that there are various theories that will support the exercise of shareholder voting in Nigeria including the option theory, agency theory, transaction cost theory, contract theory among others. In the same vein, regulators in Nigeria also need to double their effort and ensure that shareholder voting right is duly exercised. Additionally, considering the significance attached to shareholder vote, this study suggest that the CAMA 1990 should make provisions that will ensure shareholder vote is duly exercise since there is both philosophical and legal basis for the exercise of shareholder vote.